ANALISIS PENGGUNAAN ZAHIR ACCOUNTING DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (STUDI KASUS: Mahasiswa Program Studi S1 Akuntansi Universitas Pembangunan Nasional Veteran Jakarta) - Prasasti Herdiarti Putri (2021)
This study is a quantitative study that aims to determine the acceptance and use factors of Zahir Accounting. This study uses active undergraduate students of Accounting, Universitas Pembangunan Nasional Veterans Jakarta (UPNVJ) who have followed Zahir Accounting certification as samples. Sampling using random sampling method with a sample size of 100 students. Hypothesis testing in this study uses Path Coefficients by looking at t-statistics and Original Sample using the SmartPLS 3.0 program. The test results show that (1) there is a significant positive effect between computer self-efficacy on perceived usefulness, (2) there is a significant positive effect between computer self-efficacy on perceived ease of use, (3) there is an insignificant positive effect between perceived ease of use. on perceived usefulness, (4) there is a significant positive effect between perceived usefulness on attitude toward using, (5) there is a significant positive influence between perceived ease of use on attitude toward using, (6) there is a significant positive effect between attitude toward using on behavioral intention to use, and (7) there is a significant positive effect between behavioral intention to use on actual system usage.